Water saving opportunities for sustainment of irrigated agriculture: field irrigation in Turkey - Kanber R.; Ünlü M.; Koç D.L.; Kapur B.; Tekin S.; Özekici B. (Harmonization and integration of water saving options. Convention and promotion of water saving policies and guidelines, 2007)
Water scarcity has been a major concern in Turkey since the 1960's. Agriculture is the major water consuming sector with an average of 70% of the country's total water consumption. Many studies have been conducted to ensure more efficient use of water for sustainable agricultural development through better management of the irrigation schemes by the local authorities and Water Users Organizations (WUOs). Irrigated agriculture is the most effective means for making rapid increases in crop production. The results from all research activities on irrigation in Turkey have been collected in last 10-15 years and statistical aspects of the collected results are presented to supply information and knowledge on irrigation science and assessment of past and existing experiences and identifications of relevant gaps and problems in Turkey. Also, overviews of some scientific results are on main irrigation topics such as crop-water-atmosphere relationships, irrigation scheduling techniques, comparison of irrigation methods for some main crops, and irrigation system performances are presented. Efforts were carried out to collect the results of all research activities on both irrigation and water saving opportunities to sustain irrigated agriculture in Turkey, however, published data and other activities on all studies could not be obtained due to the deficiencies in the archives system. Therefore, assessment of all the conducted studies is limited. Statistical aspects of the collected results for the last 10-15 years are presented to give information in experiences on irrigation science and assessment of past and existing experiences and identifications of relevant gaps and problems in Turkey.
5. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2006/05/03-07, Malta (Malta)